Toll-Like Receptor 7 Agonist RG7854 Mediates Therapeutic Efficacy and Seroconversion in Woodchucks With Chronic Hepatitis B - Wildum, Steffen; Korolowicz, Kyle E.; Suresh, Manasa; Steiner, Guido; Dai, Lue; Li, Bin; Yon, Changsuek; De Vera Mudry, Maria Cristina; Regenass-Lechner, Franziska; Huang, Xu; Hong, Xupeng; Murreddu, Marta G.; et al. (Frontiers in Immunology, 2022)
Conventional treatment of chronic hepatitis B (CHB) is rarely curative due to the immunotolerant status of patients. RG7854 is an oral double prodrug of a toll-like receptor 7 (TLR7) agonist that is developed for the treatment of CHB. The therapeutic efficacy, host immune response, and safety of RG7854 were evaluated in the woodchuck model of CHB. Monotreatment with the two highest RG7854 doses and combination treatment with the highest RG7854 dose and entecavir (ETV) suppressed viral replication, led to loss of viral antigens, and induced seroconversion in responder woodchucks. Since viral suppression and high-titer antibodies persisted after treatment ended, this suggested that a sustained antiviral response (SVR) was induced by RG7854 in a subset of animals. The SVR rate, however, was comparable between both treatment regimens, suggesting that the addition of ETV did not enhance the therapeutic efficacy of RG7854 although it augmented the proliferation of blood cells in response to viral antigens and magnitude of antibody titers. The induction of interferon-stimulated genes in blood by RG7854/ETV combination treatment demonstrated on-target activation of TLR7. Together with the virus-specific blood cell proliferation and the transient elevations in liver enzymes and inflammation, this suggested that cytokine-mediated non-cytolytic and T-cell mediated cytolytic mechanisms contributed to the SVR, in addition to the virus-neutralizing effects by antibody-producing plasma cells. Both RG7854 regimens were not associated with treatment-limiting adverse effects but accompanied by dose-dependent, transient neutropenia and thrombocytopenia. The study concluded that finite, oral RG7854 treatment can induce a SVR in woodchucks that is based on the retrieval of antiviral innate and adaptive immune responses. This supports future investigation of the TLR7 agonist as an immunotherapeutic approach for achieving functional cure in patients with CHB.